DIAGNOSTIC ACCURACY OF ULTRASOUND IN DETECTING PERICHOLECYSTIC ADHESIONS IN CHOLELITHIASIS PATIENTS KEEPING PER-OPERATIVE FINDINGS AS THE GOLD STANDARD - Khan, Rimsha; Anwar, Sarah; Mehmood, Sadia (Pakistan Journal of Physiology, 2024)
Background: Laparoscopic cholecystectomy is a standard technique for surgical management of cholelithiasis. Dense pericholecystic adhesions pose a primary challenge during the procedure, underscoring the importance of their pre-surgical detection. While ultrasonography remains the gold standard tool for diagnosing cholelithiasis, there is limited data available regarding its diagnostic accuracy in detecting pericholecystic adhesions. This study aimed to assess the diagnostic precision of ultrasound in identifying pericholecystic adhesions. Methods: This study was carried out in the Radiology Department of DHQ Hospital, Narowal, spanning from Jul 2023, to Mar 2024. With a sample size of 138, all patients enrolled in the study underwent fasting abdominal ultrasound to identify the sonographic features of pericholecystic adhesions, including pericholecystic stranding, pericholecystic fluid/exudates, contracted gallbladder lumen, and loss of gall bladder wall/hepatic parenchyma interface. Operative findings were gathered from the Surgery Department for subsequent analysis. Results: Out of the total 138 patients, 53 (38.4%) patients were true positive, 16 (11.6%) were false positive, 49 (35.5%) were true negative and 20 (14.5%) were false negative. Ultrasonography had 72.6% sensitivity, 75.3% specificity, 76.8% positive predictive value, 71.0% negative predictive value, and 73.9% diagnostic accuracy in preoperative prediction of pericholecystic adhesions. Conclusions: Ultrasound remains an accessible and cost-effective imaging tool for identifying pericholecystic adhesions in patients with cholelithiasis. It is a valuable and reliable tool in aiding the selection of most suitable operative technique for cholecystectomy. Pak J Physiol 2024;20(2):27-30